Pan-cancer landscape of UBD/FAT10 and experimental validation in esophageal carcinoma - Zhang, Xu; Pan, Hongnian; Wang, Xiuzhong (Frontiers in Oncology, 2025)
ObjectiveTo comprehensively characterize the pan-cancer roles of Ubiquitin D (UBD/FAT10) in tumorigenesis, immune regulation, and therapeutic response through integrative multi-omics and expe+rimental analyses.MethodsUtilizing bulk RNA-seq (TCGA/GTEx/CPTAC), immune deconvolution, proteomics, and functional enrichment, we analyzed UBD expression, survival prognosis, immune infiltration, and molecular pathways across 33 cancers. Molecular docking and MD simulations were performed to assess UBD-protein interactions. Through lentivirus-mediated overexpression, functional assays (CCK-8, colony formation, wound healing, and Transwell), transcriptome sequencing, and biochemical validation, we demonstrated that UBD promotes malignant phenotypes in esophageal cancer via the TP53 signaling pathway.ResultsUBD was upregulated in 14 cancers but downregulated in thyroid carcinoma (THCA) and kidney chromophobe (KICH). ROC analysis highlighted UBD’s diagnostic potential (AUC >0.8 in gastrointestinal tumors). High UBD conferred protection in melanoma (SKCM, HR = 0.891) and sarcoma (SARC, HR = 0.899) but predicted poor outcomes in uveal melanoma (UVM, HR = 1.298) and pancreatic adenocarcinoma (PAAD, HR = 1.143).UBD positively correlated with the IFN-γ-dominant immune subtype (C2), characterized by CD8+ T cells/M1 macrophages. Drug sensitivity profiling nominated imatinib (Vina score: -8.9 kcal/mol) and TTNPB as potential therapies for UBD-high tumors, validated by stable MD simulations. In esophageal carcinoma (ESCA), UBD expression escalated with tumor stage and predicted poor survival (p<0.05).UBD enhances the proliferation and migration of esophageal cancer cells by modulating the TP53 signaling pathway, as validated through transcriptomic analysis and functional assays.ConclusionsThis study advances UBD as a prognostic indicator and therapeutic target, bridging molecular insights with clinical translation in precision oncology.